Outcomes of early versus delayed laparoscopic cholecystectomy for acute cholecystitis performed at a single institution. Issue 1 (3rd April 2018) - Kohga, Atsushi; Suzuki, Kenji; Okumura, Takuya; Yamashita, Kimihiro; Isogaki, Jun; Kawabe, Akihiro; Kimura, Taizo
Abstract: Introduction: Debate continues regarding the clinical outcomes of early laparoscopic cholecystectomy (ELC) versus delayed laparoscopic cholecystectomy (DLC) for acute cholecystitis (AC). The aim of this retrospective study was to compare clinical outcomes of ELC and DLC. Methods: This study consisted of 465 patients who had undergone laparoscopic cholecystectomy for AC between January 2000 and February 2017. Patients were divided between an ELC group (patients who underwent laparoscopic cholecystectomy within 6 days of symptom onset, n = 288) and a DLC group (patients who underwent laparoscopic cholecystectomy at least 7 days from symptom onset, n = 177), and clinical outcomes were compared. Results: Operation time (105 vs 124 min), length of postoperative hospital stay (4 vs 4 days), conversion rate (1.3% vs 10.7%), bile leak (0.3% vs 3.3%), residual calculus (2.4% vs 6.7%), and readmission (1.0% vs 6.7%) were significantly better in the ELC group. A history of upper abdominal surgery, grade II or grade III AC, preoperative percutaneous transhepatic gallbladder drainage, and time between symptom onset and surgery of more than 7 days were independent risk factors for conversion. Conclusions: ELC for AC yields more favorable clinical outcomes than DLC.